Experimental varicocoele in rats affects mechanisms that control expression and function of the androgen receptor. (9th July 2013) - Soares, T. S.; Fernandes, S. A. F.; Lima, M. L.; Stumpp, T.; Schoorlemmer, G. H.; Lazari, M. F. M.; Porto, C. S.
Summary: Varicocoele is an important cause of male infertility. Normal male reproductive function and fertility depends on a delicate balance between androgen receptor (AR) and the classic oestrogen receptors ESR1 (ERα) and ESR2 (ERβ). Using a model of surgically induced varicocoele in rats, this study aimed to investigate the effects of varicocoele on the expression of AR, ESR1, ESR2 and G‐protein coupled oestrogen receptor (GPER). Varicocoele did not affect the mRNA and protein expression of ESR1 and ESR2 in both testes. Varicocoele did not affect the mRNA and protein expression of GPER in the right testis, but slightly reduced the mRNA and increased the protein levels in the left testis. Varicocoele did not affect the mRNA for AR, but reduced the protein levels in both testes. A proteomic approach was used in an attempt to find differentially expressed targets with possible correlation with AR downregulation. Varicocoele caused the differential expression of 29 proteins. Six proteins were upregulated, including the receptor for activated C kinase 1 (RACK1), and 23 were downregulated, including dihydrolipoamide dehydrogenase, alpha‐enolase and pyrophosphatase 1. Western blot analysis confirmed that varicocoele upregulated the expression of RACK1, a protein involved with tyrosine phosphorylation and regulation of AR transcriptional activity, AR metabolism and dynamics of the blood–testis barrier. In conclusion, this study suggests that varicocoele affects mechanisms that control AR expression and function. This regulation of AR may play an important role in the varicocoele‐induced testicular dysfunction. Furthermore, varicocoele downregulates several other proteins in the testis that may be useful markers of spermatozoa function and male infertility.